Growth performance of the red-stripe weevil Rhynchophorus schach Oliv. (Insecta: Coleoptera: Curculionidae) on meridic diets - Bong, Joseph Choon Fah; Er, Chin Chin; Yiu, Pang Hung; Amarthalingam, Rajan (Science Publications, 2008)
Biology and growth performance of Red Stripe Weevil, Rhynchophorus schach Oliv. were studied using meridic diets. The diets consisted of sugarcane (Saccharum officinarum L.) bagasse, copra (Cocos nucifera L.) cake and sago (Metroxylon sagus Rottb.) flour as main ingredients. Larvae or locally known as sagoworm, in copra cake diet exhibited the fastest growth with maximum weight gain of 1609 mg in week 5, while those of sugarcane bagasse diet had slowest growth with peak weight gain of 1024 mg in week 9. Sago flour diet gave the longest larval period at 96.3 days with the highest final larval weight of 8132.1 mg. The R. schach larvae had 8 instars. Head capsule width within each instar was constant irrespective of diets given. Instar period was dependent on diets given and varied from 6.3-12 days. Pupal duration ranged from 38.5-41 days. Adult emergence was 90%. Sago flour diet had the heaviest pupae and adults. Male weevils emerged earlier than the females, but females lived 10-13 days longer. Fecundity was low at 67 eggs per female but the hatchability was 92%. Life cycle for the insect ranged from 130.2-138.8 days, with a lifespan of 178.2-183.8 days. Larvae raised on sago flour diet had the highest fat content at 57.8% but with the lowest fiber at 4.7%. Larvae were generally rich in Mg, Ca, Zn and Fe, but low in Cu. This study showed that sago flour constituted the most suitable diet. The results also suggested that growth and development of the weevil could be further improved by incorporating copra cake and sugarcane bagasse into the sago flour diet. Larvae could be readily mass produced as a source of nutritious food, besides its potential use as a laboratory test organism.